2017
DOI: 10.7150/jca.20889
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral ANXA1 Is a Predictive Marker for Sunitinib Treatment of Renal Cancer Patients

Abstract: Background and aims: There is no established predictive marker for the treatment of renal cancer. Metastatic renal cell carcinoma (mRCC) patients are often treated with sunitinib, a tyrosine kinase inhibitor. Sunitinibs anti-cancer effect is at least partly mediated through interfering with angiogenesis. Our aim with the current study was to assess annexin A1 (ANXA1), which stimulates angiogenesis, as a predictive marker for sunitinib therapy in mRCC patients. Since previous studies have indicated a predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The local Research Ethics Committee in Uppsala granted approval for the study (2009/139) and patients still alive gave their written informed consent. The TMA cohort and treatment characteristics have been described previously [11,12,21] (Table 1) [12]. In short, the TMA consists of 139 cases of RCC diagnosed 2006-2010.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The local Research Ethics Committee in Uppsala granted approval for the study (2009/139) and patients still alive gave their written informed consent. The TMA cohort and treatment characteristics have been described previously [11,12,21] (Table 1) [12]. In short, the TMA consists of 139 cases of RCC diagnosed 2006-2010.…”
Section: Patientsmentioning
confidence: 99%
“…Treatment characteristics for renal cancer patients treated for metastatic disease with sunitinib in the firstand second-line setting [12].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…examined ANXA1 cytoplasmic staining in 77 metastatic RCC cases treated with nephrectomy followed by sunitinib therapy in the first‐ or second‐line setting. Cytoplasmic ANXA1‐negative cases (25/77, 32%) showed better progression‐free survival and overall survival than cytoplasmic ANXA1‐positive cases . Niinivirta et al .…”
mentioning
confidence: 98%
“…Cytoplasmic ANXA1-negative cases (25/77, 32%) showed better progression-free survival and overall survival than cytoplasmic ANXA1-positive cases. 3 Niinivirta et al concluded that cytoplasmic expression of ANXA1 was a negative predictive marker for sunitinib treatment in metastatic RCC patients.…”
mentioning
confidence: 99%